The effects of shading and defoliation on the nodulation and nitrogen fixation of white clover (Trifolium repens L.): a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science at Massey University - Chu, Alexander Cheong Ping (Massey University, 1971)
The ability of the legume-Rhizobium symbiosis to fix atmospheric nitrogen, hence contributing towards the maintenance of soil fertility is well recognised. Although increasing usage of mineral nitrogen is evident in agricultural practices overseas (Watkin, Williams 1970), in New Zealand legume nitrogen is still by far the most important source of nitrogen in grassland farming. Nitrogen fixation in a fertile ryegrass-white clover association has been estimated to yield as much as 550 1b N Per acre per annum (Sears 1953), and it has been emphasised that for maximum benefit to the grass component in a mixed sward the white clover should be periodically defoliated and have ample light for regrowth (Butler, Greenwood &Soper 1959). The present study examines the effects of defoliation and shading on nodulation and nitrogen fixation in white clover.
Keywords: White clover; Nitrogen -- Fixation; Root-tubercles